2004
DOI: 10.1139/f04-129
|View full text |Cite
|
Sign up to set email alerts
|

Copper inhibition of phytoplankton in Saginaw Bay, Lake Huron

Abstract: Field surveys and bioassays during 1999 and 2000 demonstrated trace metal effects on the phytoplankton of inner and outer regions of Saginaw Bay, Lake Huron. Addition of as little as 1 µg·L -1 copper suppressed algal biomass, measured as particulate chlorophyll a, compared with control treatments, additions of ethylenediaminetetraacetic acid, or additions of carrier water alone. Suppression effects of copper, added alone or in combination with cadmium, lead, and thallium, were evident in inner and outer region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
(30 reference statements)
0
7
0
2
Order By: Relevance
“…Whereas copper is an essential micronutrient, at higher concentrations it is toxic to phytoplankton, hence the use of copper sulphate as an algicide in lakes and reservoirs. In a Lake Huron bioassay experiment, phytoplankton growth was inhibited by addition of as little as 1 mg/L copper, despite complexation of most of the added copper with organic ligands in the lake water (Lehman et al, 2004).…”
Section: Micronutrient Limitation In Lake Waiholamentioning
confidence: 99%
“…Whereas copper is an essential micronutrient, at higher concentrations it is toxic to phytoplankton, hence the use of copper sulphate as an algicide in lakes and reservoirs. In a Lake Huron bioassay experiment, phytoplankton growth was inhibited by addition of as little as 1 mg/L copper, despite complexation of most of the added copper with organic ligands in the lake water (Lehman et al, 2004).…”
Section: Micronutrient Limitation In Lake Waiholamentioning
confidence: 99%
“…Copper additions have been shown to reduce chl a levels in natural freshwater phytoplankton communities, other laboratory bioassays with C. reinhardtii, and higher plants [17,18,30]. One likely mechanism to explain the decrease in chlorophyll may be Cu substitution for Mg during chlorophyll formation [2].…”
Section: Bioassay Of Cell Response To Cu Exposurementioning
confidence: 99%
“…Importantly, the tools applied in this work are likely those that prove useful in advancing our understanding of cellular metal toxicity. In addition, Cu has been shown to inhibit phytoplankton growth and chlorophyll a (chl a) production in algal communities in surface waters [18]. We chose Chlamydomonas reinhardtii as our freshwater test organism because of its extensive use in laboratory experiments, documented sensitivity to Cu [15][16][17], and wellestablished genetic and molecular characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Field surveys and bioassays demonstrated trace metal effects on the phytoplankton of inner and outer regions of Saginaw Bay, Lake Huron (USA) (Lehman et al, 2004). A suggested that Hg increased with size and age of fish and showed a negative relationship with growth rate (Stafford et al, 2004).…”
Section: Heavy Metalsmentioning
confidence: 99%